KEMAMPUAN PENALARAN PROPORSIONAL DITINJAU DARI GAYA KOGNITIF SISTEMATIS DAN INTUITIF SISWA MTSN 2 BANDA ACEH - Maidiyah, Erni; Putri, Trisna Isnanda; Fadhiliani, Dwi (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2025)
Research indicated that many students, from primary to secondary levels, still struggled to develop proportional reasoning. Numerous students encountered difficulties in formulating effective problem-solving strategies due to differences in cognitive styles. It was important to assess students' proportional reasoning abilities by considering whether they had systematic or intuitive cognitive styles. This study aimed to determine the proportional reasoning abilities of students with systematic and intuitive cognitive styles. The research was a qualitative descriptive study. The subjects of this study were four students in the seventh grade at MTsN 2 Banda Aceh. Data collection techniques included written tests and interviews. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing. The results show that students with a systematic cognitive style can identify all information and quantities when understanding covariation, whereas students with an intuitive style tend to overlook some important information. Both groups recognise that the problems involve proportional situations and use the cross-multiplication strategy, but neither group can solve the problems using other strategies.